(untitled) (INNOVATIVE ECONOMY, 2025)
Prysiazhniuk N.M., Horchanok A.V., Hubanova N.L., Yakovyshyn Ya.V. FINANCIAL INSTRUMENTS FOR SUPPORTING ENTREPRENEURSHIP IN THE AQUACULTURE SECTOR: INTERNATIONAL EXPERIENCE AND UKRAINIAN REALITIES Purpose. The aim of the article is to substantiate the theoretical foundations and generalize international experience in the application of financial instruments to support entrepreneurship in aquaculture, as well as to develop practical recommendations for adapting these mechanisms to Ukrainian realities, taking into account modern social and economic challenges and the needs of the post-war restoration of the agricultural sector. Methodology of research. A set of research methods that provide a comprehensive analysis of financial instruments for supporting aquaculture is used in the article. The method of a systems approach is used to reveal the relationship between state policy, international programs and entrepreneurial initiatives. Comparative analysis allowed us to explore the differences in financing aqua-entrepreneurship between Ukraine and leading countries of the world. Based on the statistical method, the volume of financial support and its effectiveness in dynamics are analysed. The generalization method is also applied, which made it possible to formulate practical recommendations for improving the Ukrainian aquaculture support system. Findings. The results of the study showed that international experience confirms the key role of state financial support in the development of competitive aquaculture. It was found that direct financing, lending and grant programs create a multiplier effect, stimulating the attraction of private investment. In the EU, Canada and Asia, aquaculture has been transformed into a strategic sector of the economy due to active state participation. At the same time, in Ukraine financial instruments remain limited and require institutional improvement and integration of international practices. Thus, it was established that increasing the effectiveness of financial support mechanisms is a key prerequisite for activating the entrepreneurial potential of aquaculture. Originality. For the first time, the mechanisms of state and international support for the development of aqua-entrepreneurship (budget subsidies, credit instruments, grant programs, risk insurance) were generalized and organized from the standpoint of their impact on increasing the investment attractiveness of the industry. The peculiarities of the functioning of financial instruments in Ukraine were identified and it was substantiated that their further improvement requires the implementation of the most effective international approaches. The conceptual principles of a synergistic combination of state support and private capital as a key factor in the long-term and sustainable development of entrepreneurship in the aquaculture sector were developed. Practical value. The practical application of state support mechanisms will allow creating an effective system of financial support for aquaculture, focused on long-term investment growth and sustainability of the industry. The introduction of specialized credit programs for fish farming will ensure the availability of loan capital for small and medium-sized producers, and the formation of a national aquaculture development fund will allow accumulating targeted resources for the modernization of the production base. The introduction of an aqua insurance system will help minimize environmental and market risks and increase the investment reliability of the sector. Stimulating cooperative and cluster models will help increase efficiency, reduce transaction costs, and expand sales opportunities. The integration of aquaculture into global green financing programs opens up opportunities for attracting ESG investments and issuing “green” bonds, which will allow diversifying sources of financial revenues and forming a sustainable financial basis for the development of aqua entrepreneurship. Key words: aquaculture, financial instruments, entrepreneurship, state support, investments, international experience, food security, lending, grant programs.